2018
DOI: 10.4251/wjgo.v10.i10.293
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous curative resection of double colorectal carcinoma with synchronous bilobar liver metastases

Abstract: Synchronous colorectal carcinoma (SCRC) indicates more than one primary colorectal carcinoma (CRC) discovered at the time of initial presentation, accounts for 3.1%-3.9% of CRC, and may occur either in the same or in different colorectal segments. The accurate preoperative diagnosis of SCRC is difficult and diagnostic failures may lead to inappropriate treatment and poorer prognosis. SCRC requires colorectal resections tailored to individual patients, based on the number, location, and stage of the tumours, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 178 publications
(367 reference statements)
0
5
0
Order By: Relevance
“…In this regard, a recent study conducted in 2021 by Dyre Kleive et al [15], states that simultaneous colorectal and hepatic resection should be avoided when major resections are required, both hepatic and colo-rectal and should be further subject of clinical trials. It is clear that a good postoperative prognostic factor in the simultaneous approach is the size of liver metastases and the extent of liver resection, confirmed in most studies [16,17,18,19].…”
Section: Discussionmentioning
confidence: 83%
“…In this regard, a recent study conducted in 2021 by Dyre Kleive et al [15], states that simultaneous colorectal and hepatic resection should be avoided when major resections are required, both hepatic and colo-rectal and should be further subject of clinical trials. It is clear that a good postoperative prognostic factor in the simultaneous approach is the size of liver metastases and the extent of liver resection, confirmed in most studies [16,17,18,19].…”
Section: Discussionmentioning
confidence: 83%
“…Altogether, these data demonstrate that CRLM may be well-circumscribed, with a very low incidence of satellite nodules or micrometastases, suggesting a limited effect of minimal negative RM on recurrence or survival rates in selected patients[ 6 , 24 ]. Pawlik et al[ 134 ] have reported that OS and DFS, overall recurrence risk and site of recurrence were similar after resection of CRLM with margins of 1-4 mm, 5-9 mm, and ≥ 10 mm, suggesting that a predicted RM of < 1 cm should not contraindicate liver surgery.…”
Section: Parenchymal-sparing Liver Resectionmentioning
confidence: 95%
“…A complete response of the rectal tumour to CHRT after initial liver surgery has been occasionally described, thus delaying or even avoiding the planned rectal resection[ 78 ]. However, simultaneous colorectal and liver resection represents the most attractive strategy, with growing consensus and a progressive expansion of resectability criteria[ 6 , 28 ]. Simultaneous resections improve the patient experience, by reducing the number of surgical procedures and also the duration of perioperative CHT in selected cases[ 4 , 17 ], and may substantially decrease the cumulative costs of hospitalization[ 79 ].…”
Section: Therapeutic Strategies For Synchronous Colorectal Liver Metamentioning
confidence: 99%
See 2 more Smart Citations